If x 2 − x + 1 = 0 , then find the value of ( x − x 1 ) 2 + a = 1 ∑ 2 0 1 5 ( x a + x a 1 ) 2
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
note that for x = − 1
we have x 3 − x 2 + x = 0 and x 2 − x + 1 = 0
sum that both
x 3 + 1 = 0 or x 3 = − 1 for x = − 1
then note that x = 0 divide that LHS and RHS by x
we have x + x 1 = 1
squared that LHS and RHS also we have x 2 + x 2 1 = − 1
∙ case 1
( x − x 1 ) 2 = x 2 + x 2 1 − 2 = − 1 − 2 = − 3
∙ case 2
( x 3 k + x 3 k 1 ) 2 = ( ( x 3 ) k + ( x 3 ) k 1 ) 2 = ( 1 + 1 ) 2 = 4 for some k ∈ N
( x 3 k + 1 + x 3 k + 1 1 ) 2 = ( x ( x 3 ) k + x ( x 3 ) k 1 ) 2 = ( x + x 1 ) 2 = x 2 + x 2 1 + 2 = − 1 + 2 = 1 for some k ∈ N ∪ { 0 }
( x 3 k + 2 + x 3 k + 2 1 ) 2 = ( x 2 ( x 3 ) k + x 2 ( x 3 ) k 1 ) 2 = ( x 2 + x 2 1 ) 2 = ( − 1 ) 2 = 1 for some k ∈ N ∪ { 0 } then ( x − x 1 ) 2 + ( x + x 1 ) 2 + ( x 2 + x 2 1 ) 2 + ( x 3 + x 3 1 ) 2 + . . . + ( x 2 0 1 5 + x 2 0 1 5 1 ) 2
= − 3 + 4 ⌊ 3 2 0 1 5 ⌋ + 1 ( 2 0 1 5 − ⌊ 3 2 0 1 5 ⌋ ) = 4 0 2 5
t h e r o o t s a r e − ω a n d − ω 2 s u b s t i t u t e i n t h e f i r s t t e r m y o u g e t − 3 a n d o t h e r t e r m s o f p o w e r s d i v i s i b l e b 3 w i l l g i v e ( − 1 − 1 ) 2 = 4 s o n u m b e r o f t e r m s o f p o w e r s d i v i s i b l e b y 3 i s 3 2 0 1 3 = 6 7 1 a n d t h e o t h e r t e r m s g i v e 1 2 s o t h e f i n a l r e s u l t = − 3 + 6 7 1 ( 4 ) + ( 2 0 1 5 − 6 7 1 ) ( 1 ) = 4 0 2 5
since x is -w or -w^2 putting x as -w and expanding all brackets and forming GP we get the required sum as 4030-2-3=4025
note: w is cube root of unity
Consider f ( x ) = x 3 + 1 .
Then we have that x + 1 x 3 + 1 = x 2 − x + 1 and so the roots of x 2 − x + 1 are the complex roots of x 3 + 1 which are ω 1 = e i 3 π and ω 2 = e − i 3 π = ω 1 1 .
We have to evaluate the expression ( x − x 1 ) 2 + ∑ a = 1 2 0 1 5 ( x a + x a 1 ) 2 for x = ω 1 or x = ω 2 ,
but it is clear this expression does not change if we exchange ω 1 and ω 2 and so we could evaluate the expression just for x = ω 1 .
The first term is equal to ( 2 ∗ ℑ e i 3 p i ) 2 = ( 2 sin ( 3 p i ) ) 2 = ( i ( 3 ) ) 2 = − 3 .
For the second term, note that we could rewrite it as
∑ a = 1 2 0 1 5 ω 1 2 a + ∑ a = 1 2 0 1 5 ω 2 2 a + ∑ a = 1 2 0 1 5 2 .
Using the formulae for the sum of a geometric progression, we found that it is equal to
( ω 1 2 − 1 ω 1 2 ∗ 2 0 1 6 − 1 − 1 ) + ( ω 2 2 − 1 ω 2 2 ∗ 2 0 1 6 − 1 − 1 ) + 2 ∗ 2 0 1 5 .
Now ω 1 2 ∗ 2 0 1 6 = ω 1 2 ∗ 3 ∗ 6 7 2 = ( ω 1 3 ) 2 ∗ 6 7 2 = ( − 1 ) 2 ∗ 6 7 2 = 1 .
In the same way ω 2 2 ∗ 2 0 1 6 = 1 .
Thus the second term simplifies to ( 0 − 1 ) + ( 0 − 1 ) + 2 ∗ 2 0 1 5 = 4 0 2 8 .
Finally − 3 + 4 0 2 8 = 4 0 2 5 .
Problem Loading...
Note Loading...
Set Loading...
If x 2 − x + 1 = 0 . Then by quadratic formula x = 2 1 + i 2 3 or x = 2 1 − i 2 3 .
( x − x 1 ) 2 + ( x + x 1 ) 2 + ( x 2 + x 2 1 ) 2 + ( x 3 + x 3 1 ) 2 + . . . + ( x 2 0 1 5 + x 2 0 1 5 1 ) 2
= ( x − x 1 ) 2 + ∑ n = 1 2 0 1 5 ( x n + x n 1 ) 2 .
Let x = cos 6 0 ∘ + i sin 6 0 ∘ .
( cos 6 0 ∘ + i sin 6 0 ∘ − cos 6 0 ∘ + i sin 6 0 ∘ 1 ) 2 + ∑ n = 1 2 0 1 5 ( ( cos 6 0 ∘ + i sin 6 0 ∘ ) n + ( cos 6 0 ∘ + i sin 6 0 ∘ ) n 1 ) 2 =
( cos 6 0 ∘ + i sin 6 0 ∘ − ( cos 6 0 ∘ − i sin 6 0 ∘ ) ) 2 + ∑ n = 1 2 0 1 5 ( cos ( 6 0 n ) ∘ + i sin ( 6 0 n ) ∘ + cos ( 6 0 n ) ∘ + i sin ( 6 0 n ) ∘ 1 ) 2 =
( 2 i sin 6 0 ∘ ) 2 + ∑ n = 1 2 0 1 5 ( cos ( 6 0 n ) ∘ + i sin ( 6 0 n ) ∘ + cos ( 6 0 n ) ∘ − i sin ( 6 0 n ) ∘ ) 2 =
− 4 sin 2 6 0 ∘ + ∑ n = 1 2 0 1 5 ( 2 cos ( 6 0 n ) ∘ ) 2 =
− 4 ( 2 3 ) 2 + ∑ n = 1 2 0 1 5 4 cos 2 ( 6 0 n ) ∘ =
− 3 + 4 ∑ n = 1 2 0 1 5 cos 2 ( 6 0 n ) ∘ = .
Cosine is a cyclic function so the values of cos ( 6 0 n ) ∘ repeat every six times because 6 0 3 6 0 = 6 . 2015 mod 6 is 5 so the sum of the first six terms of the original summation repeats 335 times with 5 left over or 336 times minus the last value. The equation then becomes.
− 3 − cos 2 ( 3 6 0 ) ∘ + 4 ∑ n = 1 3 3 6 cos 2 ( 6 0 ) ∘ + cos 2 ( 1 2 0 ) ∘ + cos 2 ( 1 8 0 ) ∘ + cos 2 ( 2 4 0 ) ∘ + cos 2 ( 3 0 0 ) ∘ + cos 2 ( 3 6 0 ) ∘ =
− 3 - 1 2 + 4 ∑ n = 1 3 3 6 ( 2 1 ) 2 + ( 2 − 1 ) 2 + ( − 1 ) 2 + ( 2 − 1 ) 2 + ( 2 1 ) 2 + ( 1 ) 2 =
− 7 + 4 ∑ n = 1 3 3 6 3 = − 7 + 1 2 ∑ n = 1 3 3 6 1 = − 7 + 1 2 ∗ 3 3 6 = 4 0 2 5 .